Missed Diagnosis of a Heterotopic Pregnancy with Tubal Rupture: A Case Report - Sharma, B (Nepal Journal of Obstetrics and Gynaecology, 2014)
We report a combined intra-uterine and ruptured tubal pregnancy following ovulation induction by clomiphene citrate(CC).She was a 35 year old multigravida who presented with a ruptured tubal pregnancy and underwent right salphingectomy. Three months later, she presented with amenorrhea from the time of operation and an intra-uterine pregnancy was confirmed. Previous ultrasound at her initial presentation, did not reveal an intra-uterine pregnancy. The second ultrasound dating indicated that the intra-uterine conception had occurred before the tubal pregnancy was diagnosed. Therefore, a high index of suspicion for heterotopic pregnancy is needed in woman taking ovulation inducing drugs. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11142 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 40-42